Peran Keluarga dalam Meningkatkan Self Care Agency Pada Klien DM Tipe II - hakim tobroni HR; Sonti Kogoya (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Self-care in patients with diabetes mellitus is something that is very important because it acts as a disease control (blood sugar increase) and prevents complications, so there needs to be a family role in controlling blood sugar. The purpose of the study was to describe the role of families in improving the self-care agency of type II diabetes mellitus clients at Amelia Pare Hospital. This research uses qualitative methods with a phenomenological study approach. The population of this study was a family of clients in the internal medicine room who had family members with type II diabetes mellitus at Amelia Pare Hospital with a sample number of 4 participants with purposive sampling techniques. Data analysis techniques use qualitative descriptive. The results of the study obtained family experience in improving the ability of self-care to have different ways and coping, as well as understanding in identification, problem-solving and confectionery differently each participant. The analysis of this study produced a theme about the way families improve self-care agencies, among others; 1) Understanding self care agency, 2) Components in Improving Self Care Agency, 3) How to Improve Self Care Agency, 4) Problems in Improving Self Care Agency. Efforts of people with type II diabetes mellitus can be in the form of discussions with close family or health services that are trusted in overcoming problems suffered by clients.